The Effect of Non-Physical Work Environment, Motivation, and Workload on Employee Performance with Job Satisfaction as an Intervening Variable on Perum DAMRI MAC Bus Drivers - Amal Fazri Nur Ridwan; Gurawan Dayona Ismail; Asti Nur Aryanti; Ridlwan Muttaqin; Recky Recky (Eduvest - Journal of Universal Studies, 2026)
Employeeoperformance isothe level of success or workoresults achievedoby anoindividual inocarrying outotheir dutiesoand responsibilities during a certain period, which is measured based on standards or targets set by the organization. Theopurpose ofothis studyois toodetermine the analysis of non-physical work enviironment, motivation, and workload on employeoperformance withojob satisfactionoas an interveningovariable. Theoresearch methodoused inothis studyois a quantitativeoresearch method with a descriptiveoandoverification approach. Dataocollection techniques in thisostudy are interviews, questionnaires, andoobservations with a population of 90 drivers. Theosampling techniqueoused in thisostudy is a non-probability samplingotechnique with sensus sampling. The analytical tool in thisostudy is SmartPLS 4 for verification analysis. Testing of measurement models or outer models in this study is convergentovalidity, discriminantovalidity, AverageoVariance Extractedo (AVE), compositeoreliability, Cronbachoalpha. The structural model or inner models tested in this study were the coefficientoof determinationo (R2) and predictiveorelevance (Q2). Theoresults of thisostudy indiicate thatothe non-physiical work enviironment and motivation have a positiive and signiificant effectt on job satisfactiion partially, while workload has no effectt on job satisfactiion partially. Workload and satiisfaction have a posiitive and signifiicant effectt on peerformance, while the non-physiical work enviironment and motiivation have nooeffect onoperformance partially. Simultaneously, the effect is 76.1%, and the remaiining 23.9% is inflluenced by other facttors. Job satisfaction can mediate the non-physiical work enviironment and motivation on emplloyee perforrmance, but cannot mediate the effect of workload on emplloyee peerformance.